Gaps in knowledge and use of artemether-lumefantrine among university students in Southwestern Nigeria: A cross-sectional study - Edidiong Orok; Oluwaseun Olumoko; Inimuvie Ekada; Amos Oladunni (PLoS ONE, 2026)
Inappropriate use of antimalarial medications can accelerate the development of antimicrobial resistance (AMR), undermining treatment efficacy and public health goals. Artemether-lumefantrine (A/L) is the first-line treatment for uncomplicated malaria in Nigeria, yet its misuse persists, particularly among young adults. This study assessed knowledge gaps in A/L use among university students in Southwestern Nigeria to identify opportunities for targeted intervention. A cross-sectional online survey was conducted among undergraduate students from three universities in Southwestern Nigeria. Respondents’ knowledge of A/L was categorized as good (≥70%), fair (50–69%), or poor (<50%). Associations between knowledge and demographic or experiential variables were analysed using independent sample t-tests and one-way ANOVA, with significance set at p < 0.05. Data analysis was performed using SPSS version 27. A total of 392 students participated, with a mean age of 19.5 years; 58.4% were female. While 64.5% knew the correct timing for the second dose of A/L, only 22.2% correctly identified appropriate storage methods. About 94.9% preferred swallowing the drug with water after food, but many were unaware of common side effects or appropriate responses. Overall, 44.6% of students demonstrated poor knowledge of A/L use. Knowledge scores differed significantly by level of study (p = 0.001) and previous use of antimalarials (p = 0.04). Substantial knowledge gaps and misconceptions about A/L use exist among university students in Southwestern Nigeria. These findings underscore the urgent need for health education initiatives targeting young adults to promote safe and effective use of antimalarial medications and may inform health education strategies aimed at promoting rational antimalarial use and strengthening malaria control efforts.